Variability in penile duplex ultrasound international practice patterns, technique, and interpretation: an anonymous survey of ISSM members. Issue 5 (October 2018) - Butaney, Mohit; Thirumavalavan, Nannan; Hockenberry, Mark; Kirby, E.; Pastuszak, Alexander; Lipshultz, Larry
Abstract Penile duplex ultrasound (PDU), combined with pharmacologic stimulation of erection, is the gold standard for the evaluation of multiple penile conditions. A 30-question electronic survey was distributed to members of the International Society for Sexual Medicine (ISSM). The survey assessed the variability in current PDU practice patterns, technique, and interpretation. Chi-square test was used to determine the association between categorical variables. Approximately 9.5% of all 1996 current ISSM members completed the survey. Almost 80% of members surveyed reported using PDU, with more North American practitioners utilizing PDU than their European counterparts (94% vs 69%, p  < 0.01). Approximately 62% of PDU studies were performed by a urologist and more than 76% were interpreted by a urologist. Although almost 90% of practitioners reported using their own protocol, extreme variation in the technique existed among respondents. Over ten different pharmacologic mixtures were used to generate erections, and 17% of respondents did not repeat dosing for insufficient erection. Urologists personally performing PDU were more likely to assess the cavernosal artery flow using recommended techniques with the probe at the proximal penile shaft (73% vs 40%) and at a 60-degree angle or less (68% vs 36%) compared with non-urologists (p  < 0.01). Large differences in PDU diagnostic thresholds were apparent. Only 38% of respondents defined arterial insufficiency with a peak systolic velocity < 25 cm/s, while 53% of respondents defined venous occlusive disease with an end diastolic velocity > 5 cm/s. This is the first study to assess the variability in the PDU protocol and practice patterns, and to pinpoint areas of improvement. As in other surveys, recall bias, generalizability, and response rate (9.5%) are inherent limitations to this study. Although most respondents report utilizing a standardized PDU protocol, widespread variation exists among practitioners in terms of both technique and interpretation, limiting accurate diagnosis and appropriate treatment of penile conditions.